Examining the relationship of teacher perception of accountability and assessment policies on teacher turnover during NCLB - Wronowski, Meredith L.; Urick, Angela (Education Policy Analysis Archives, 2019)
The purpose of this study is to determine the relationship between teachers’ perception of their work, their intent to leave their current position, and their realized turnover at the height of the federal accountability policy era in the United States. The study uses a framework of teacher de-professionalization and demoralization operationalized by teacher responses to the Schools and Staffing Surveys and Teacher Follow-up Surveys from the National Center for Education Statistics. We tested the relationship of de-professionalization and demoralization to turnover with two competing structural equation models for teachers who cited accountability policies as a factor in their employment decision, and those who did not. We find that teacher worry and stress associated with demoralization is a significant predictor of intent to leave in both groups of teachers. However, teacher worry and stress is only a significant predictor of teachers leaving the profession and moving schools in teachers who cite accountability policies as a factor in their employment decision. These findings demonstrate a relationship between teachers’ perceptions of accountability policies, perception of their working conditions, and turnover. These results have important implications for policy makers and educational leaders as the U.S. transitions from the No Child Left Behind era to the implementation of the Every Student Succeeds Act.